Violence Against Women in Rural Greece - Andreadou, Despoina; Chatzifotiou, Sevaste (Social Cohesion and Development, 2024)
Violence against women is a global human rights violation. Despite this, there is a lack of culturally sensitive country specific empirical research on violence against women. Much of the existing research focuses on the experiences of women living in urban and metropolitan areas. Little is known about the experiences of women living in rural areas. The current study uses feminist qualitative methodology to examine the unique experiences of intimate partner violence survivors in rural Greece who sought services from a regional Community Centre. Interviews with 12 rural Greek women were conducted, transcribed, and thematically coded to reveal commonalities in the participants’ narratives. Our analysis revealed themes related to the impact of rurality on help-seeking behaviors, knowledge of and access to social services, and how rural patriarchal culture impacts victims’ willingness to seek help. The results of this study shed light on the understudied experiences of rural Greek women who have experienced domestic abuse. Our findings can be used to further expand global rural criminological theory and develop procedures to remove the barriers that rural survivors face when seeking social services.